Nutrient deficiency limits population development, yield formation, and nutrient uptake of direct sown winter oilseed rape - Yin WANG; Tao LIU; Xiao-kun LI; Tao REN; Ri-huan CONG; Jian-wei LU (Journal of Integrative Agriculture)
Direct-sowing establishment method has great significance in improving winter oilseed rape (Brassica napus L.) production and guaranteeing edible oil security in China. However, nutrient responses on direct sown winter oilseed rape (DOR) performance and population development dynamic are still not well understood. Therefore, five on-farm experiments were conducted in the reaches of the Yangtze River (RYR) to determine the effects of nitrogen (N), phosphorus (P), and potassium (K) deficiencies on population density, dry matter production, nutrient uptake, seed yield, and yield components of DOR plants. Four fertilization treatments included the balanced NPK application treatment (NPK, 180 kg N, 39.3 kg P, 100 kg K, and 1.8 kg borax ha−1) and three nutrient deficiency treatments based on the NPK treatment, i.e., –N, –P, and –K. The results indicated that DOR population density declined gradually throughout the growing season, especially at over-wintering and pod-development stages. Nutrient deficiency decreased nutrient concentration in DOR plants, limited dry matter production and nutrient uptake, and thereby exacerbated density reduction during plants growth. The poor individual growth and reduced population density together decreased seed yield in the nutrient deficiency treatment. Averaged across all the experiments, seed yield reduced 61% by N deficiency, 38.3% by P deficiency, and 14.4% by K deficiency. The negative effects of nutrient deficiency on DOR performances followed the order of –N>–P>–K, and the effects were various among different nutrient deficiencies. Although N deficiency improved DOR emergence, but it seriously limited dry matter production and nutrient uptake, which in turn led to substantial plants death and therefore resulted in a very low harvested density. The P deficiency significantly reduced initial density, limited plants growth, and exacerbated density reduction. The K deficiency mainly decreased individual growth and yield, but did not affect density dynamic. Our results highlighted the importance of balanced NPK application in DOR production, suggesting that management strategy of these nutrients should be comprehensively considered with an aim to build an appropriate population structure with balanced plant density and individual growth.